A case series of cerebral venous thrombosis as the first manifestation of homocystinuria. (December 2021) - Ochoa-Ferraro, Antonio; Wanninayake, Subadra; Dawson, Charlotte; Gerrard, Adam; Preece, Mary Anne; Geberhiwot, Tarekegn
Background: Cerebral venous thrombosis (CVT) is an important cause of stroke particularly in younger patients and potentially fatal if diagnosis is delayed. The presentation of symptoms is highly variable and consequently the diagnosis and underlying cause is often delayed or overlooked. Homocystinuria, a rare autosomal recessive disorder is an identified risk factor for CVT. Purpose: A timely diagnosis and treatment of the underlying cause of CVT could result in improved outcome and prevent further events. This case series describes the clinical course of six adults presented with unprovoked CVT, in whom the diagnosis of underlying homocystinuria was delayed with adverse consequences. We aim to highlight the importance of recognising homocystinuria as an underlying cause of CVT and offer a practical approach to the diagnosis and management. Methods: This is a retrospective case series of a cohort of 30 consecutive patients seen in a UK tertiary referral centre. Result: Six out of 30 patients presented with CVT prior to homocystinuria diagnosis. The mean and range of age at the time of the first CVT episode was 22.6 (range 11–31) years. The mean ±SD age at diagnosis of homocystinuria as the underlying cause was 26 ± 4.2 years. The time between first CVT and diagnosis of homocystinuria ranged from 1.6 to 11 years resulting in a delay to introduction of effective treatment and, in some cases, a further large vessels thrombotic event. Conclusion: Physician awareness of homocystinuria as an underlying cause for an unprovoked CVT will facilitate timely introduction of effective treatment to prevent a further event.